Exploring the relationship between peer feedback, writing and self-actualization in tertiary level EFL students - Rubini Radza; Rohaya binti Abdullah (Universitas Syiah Kuala, 2026)
This study was conducted to investigate the impact of peer feedback on writing skills and self-actualization, to address a research gap, particularly where the combination of these variables is underexplored. A qualitative research design that employs purposive sampling methods, document analysis, and in-depth interview sessions was adopted in this study. The participants were 10 international students from 10 different countries who were studying at a private higher learning institution in Kedah, Malaysia. The participants wrote essays, feedback, and reflective journals, and went through a one-on-one interview session. Based on the results gained from thematic analysis, this study showed that different participants respond differently (positive, negative, and neutral) to peer feedback (PF); some students agree that PF could have a significant impact on their writing skills and self-development as feedback givers as well as receivers. A few students struggled with accepting the ideas of others. They responded defensively in writing, while some students expressed that PF does not affect their writing performance or personal development. The fundamental findings of this study demonstrated that the practice of PF in EFL classrooms in the mentioned context should be cultivated as a continued practice to ensure familiarity with its techniques and to benefit from its usage by enhancing writing skills.